The joint evolutionary histories of Wolbachia and mitochondria in Hypolimnas bolina - Roderick George K (BMC Evolutionary Biology, 2009)
Abstract Background The interaction between the Blue Moon butterfly, Hypolimnas bolina, and Wolbachia has attracted interest because of the high prevalence of male-killing achieved within the species, the ecological consequences of this high prevalence, the intensity of selection on the host to suppress the infection, and the presence of multiple Wolbachia infections inducing different phenotypes. We examined diversity in the co-inherited marker, mtDNA, and the partitioning of this between individuals of different infection status, as a means to investigate the population biology and evolutionary history of the Wolbachia infections. Results Part of the mitochondrial COI gene was sequenced from 298 individuals of known infection status revealing ten different haplotypes. Despite very strong biological evidence that the sample represents a single species, the ten haplotypes did not fall within a monophyletic clade within the Hypolimnas genus, with one haplotype differing by 5% from the other nine. There were strong associations between infection status and mtDNA haplotype. The presence of wBol1 infection in association with strongly divergent haplotypes prompted closer examination of wBol1 genetic variation. This revealed the existence of two cryptic subtypes, wBol1a and wBol1b. The wBol1a infection, by far the most common, was in strict association with the single divergent mtDNA haplotype. The wBol1b infection was found with two haplotypes that were also observed in uninfected specimens. Finally, the wBol2 infection was associated with a large diversity of mtDNA haplotypes, most often shared with uninfected sympatric butterflies. Conclusion This data overall supports the hypothesis that high prevalence of male-killing Wolbachia (wBol1) in H. bolina is associated with very high transmission efficiency rather than regular horizontal transmission. It also suggests this infection has undergone a recent selective sweep and was introduced in this species through introgression. In contrast, the sharing of haplotypes between wBol2-infected and uninfected individuals indicates that this strain is not perfectly transmitted and/or shows a significant level of horizontal transmission.